HUKUM MENIKAHKAN ANAK PEREMPUAN DENGAN ORANG YANG TIDAK DIINGINKAN MENURUT SYAIKH ALI JUM'AH - Afadi, Ahmad Alfin (Al Hakam : The Indonesian Journal of Islamic Family Law and Gender Issues, 2024)
This article is about parents forcing their children to marry unwanted people reflects the need to protect individual rights and ensure a healthy marriage relationship. This article discusses the law of parents who marry their children to people who are not wanted from the point of view of the Mufti of Egypt, Sheikh Ali Jum'ah. This article uses qualitative research methods with the primary source of book al-Bayān limā Yusghilu al-Adzhān by Sheikh Ali Jum'ah. Marriages built on love and family agreement between two individuals have the potential to create strong and sustainable bonds. Conversely, coercion in marriage can damage the dynamics of the relationship, hurt the psychological and emotional well-being of children, and cause conflict in the family. Therefore, Shaykh Ali Jum'ah is firm in prohibiting all forms of coercion on children to marry those he does not want; parents only have the right to direct, not determine, the life partner of their children. This article is expected to answer the problems that occur in the community so that people understand that children have the right to choose their life partner.